Struktur Komunitas Collembola di Perkebunan Kelapa Sawit Desa Jawa Tongah II Kecamatan Hatonduhan Kabupaten Simalungun - Silaen, Srinatalia (Life Science, 2020)
Collembola is one of the soil mesofauna which is abundant in the soil which plays a major role in the food chain such as in the decomposition process of organic matter even though the role is played indirectly. The purpose of this study was to determine the evenness index, relative density, the relationship between physical & chemical factors of the environment around PTPN IV Tonduhan. The stages of this research method using random sampling, namely the Pitfal trap. The highest number of species in the Isotomidae family, namely Isotomiella sp. (17 ind) & Folsomides sp. (2ind). The highest number of individuals Isotomiella sp. (14 ind) family Isotomidae. Collembola community composition consists of 3 families & 4 species: Neanuridae (Lobella sp.), Brachystomellidae (Brachystomella sp.) & Isotomidae (Isotomiella sp. & Folsomides sp.), Collembola community structure. The highest density is in the litter location I (16 ind / m2) while the lowest density is in location III (3.56 ind / m2). The highest soil density is in location I (4,538.56 ind / m3) & the lowest density is in location III (789,761 ind / m3). The highest relative density is location III (100%) & the lowest relative density is found in location I (litter, 5.8%) & (soil, 8.9%). The highest Shannon-Wiener diversity index, both litter and soil, were found in location I (litter 1.28) & (soil, 1.38) and the lowest diversity index was found in location III (0). The highest similarity index for Sorensen was location III (75.71%) and the lowest was the comparison between locations II & I (20%). Collembola merupakan salah satu mesofauna tanah yang jumlahnya melimpah di dalam tanah berperan besar dalam rantai makanan seperti dalam proses dekomposisi bahan organik meskipun peranan dilakukan secara tidak langsung. Tujuan penelitian ini untuk mengetahui indeks kemerataan, kepadatan relatif, hubungan faktor fisik & kimia lingkungan sekitar PTPN IV Tonduhan. Tahapan metode penelitian ini menggunakan random sampling yaitu Pitfal trap. Jumlah spesies terbanyak famili Isotomidae yakni Isotomiella sp. (17 ind) & Folsomides sp. (2ind). Jumlah individu terbanyak Isotomiella sp. (14 ind) famili Isotomidae. Komposisi komunitas Collembola terdiri atas 3 famili & 4 spesies: famili Neanuridae (Lobella sp.), Brachystomellidae (Brachystomella sp.) & Isotomidae (Isotomiella sp. & Folsomides sp.), struktur komunitas Collembola Kepadatan tertinggi di serasah lokasi I (16 ind/m2) sedangkan kepadatan terendah di lokasi III (3,56 ind/m2). Kepadatan tertinggi di tanah lokasi I (4.538,56 ind/m3) & kepadatan terendah di lokasi lokasi III (789,761ind/m3). Kepadatan relatif tertinggi lokasi III (100%) & kepadatan relatif terendah ditemukan lokasi I (serasah, 5,8%) & (tanah, 8,9%). Indeks diversitas Shanon-Wiener tertinggi baik serasah maupun tanah sama-sama ditemukan lokasi I (serasah 1,28) & (tanah, 1,38) & indeks diversitas terendah sama-sama ditemukan lokasi III (0). Indeks similaritas Sorensen tertinggi lokasi III (75,71%) & terendah perbandingan antara lokasi II & I (20%).